EFEKTIFITAS TEKNIK NYANYIAN DALAM MENINGKATKAN KEMAMUAN MENGENAL TEMPAT IBADAH PADA ANAK TUNAGRAHITA RINGAN - Eka Putri Meli (Jurnal Penelitian Pendidikan Khusus, 2012)
The research is motivated by the results of treament mild mental retardation in children DII class C in SDLB N 20 huts II Pariaman totaling three people, not able to recognize the place of worship (islam-mosque, Christian churches, Hindu-temple, Buddhist temples). Metodolongi research is action research (Classroom Action Researh). Data on children's ability gained through observation and tests. Subjects were three children, mild mental retardation DII class C in SDLB N Cottage II Pariaman. (Ar, mg and ik). The research process was conducted in two cycles, namely cycle I and cycle II. Implementation cycle starts from the first and second cycles to use traditional singing technique as a tool for teaching children to know the place of worship for mental retardation. Based on these results it can be concluded that the technique of singing can be used as an effort to improve the ability to know the names of the child's place of worship for mild mental retardation.